Ù…Ø´ÙƒÙ„Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ù…Ø¹Ø§Ø±Ù ÙƒØ§Ø±Ø§Ù†Ø¬ Ø£Ù†ÙŠØ§Ø± Ø¨ÙƒØ§Ù„ÙˆÙ†Ø¬Ø§Ù† - Faliqul Isbah; Intan Kharisatun Nisak (UIN Fatmawati Sukarno Bengkulu, 2023)
This research is motivated by the difficulty faced by many students in reading Arabic texts, such as difficulties in pronouncing certain Arabic letters like (Ø´) becoming (Ø³), (Ø¶) becoming (Ø¸), and other pronunciation errors. Therefore, it is necessary to delve deeper into the problem of learning reading skills and find solutions to overcome these problems.This research is descriptive qualitative in nature, using data collection techniques including interviews, observations, and documentation. The data analysis techniques used in this research include data reduction, data presentation, and drawing conclusions. The main data were obtained from Arabic language teachers and students, supported by data from the head of the madrasah and related parties.The results of this study show that the problems of learning Arabic language are both linguistic and non-linguistic. The findings indicate that the linguistic problem in learning reading skills is the lack of understanding of students about the makharij al huruf and the pronunciation rules of the Arabic language. Meanwhile, the non-linguistic problem is related to students' motivation to learn Arabic language, their educational background, and the support of the madrasah management. The solutions to these problems include motivating students, encouraging them to read the Quran, and coordinating with the madrasah management.